A reliable and valid measurement scale for assessing internal crisis communication. Issue 2 (7th June 2019) - Adamu, Adamu Abbas; Mohamad, Bahtiar
Abstract : Purpose: There appears to be a growing concern over the lack of scales for measuring internal crisis communication (ICC) in the course of an organizational crisis. Noting this compelling evidence, an analysis of results from earlier exploratory studies demonstrated a strong need for a sound scale with adequate psychometric properties. On that account, the purpose of this paper is to develop a valid scale for ICC. Design/methodology/approach: This study examined the conceptualization and operationalization of ICC based on a comprehensive literature search. The in-depth interviews consist of 12 key informants with a sample size of 251 respondents for scale development and testing wherein all data items were evaluated and validated by 13 expert reviewers. Findings: The results were measured during a crisis situation and provided rationale and initial psychometric properties of ICC. Exploratory and confirmatory analyses have provided evidence that ICC scale has achieved a valid and reliable factor structure. Practical implications: Therefore, practitioners such as policy makers, government, researchers and crisis managers can adopt this scale of assessment to enhance a more accurate ICC; in this regard, provide useful implications to help minimize risks as they happen, thereupon find a better way to manage crisis situations. Originality/value: This study contributes to the subject area and builds the existing literature by developing 11 items for ICC. The research provides a starting point for empirical investigation on important factors of influence on organizational internal stakeholders.